Effect of aspirin on cardiovascular events and bleeding in the healthy elderly - McNeil, J.; Wolfe, R.; Woods, R.; Tonkin, A.; Donnan, G.; Nelson, M.; Reid, Christopher; Lockery, J.; Kirpach, B.; Storey, E.; Shah, R.; Williamson, J.; et al. (Massachusetts Medical Society, 2018)
Background: Aspirin is a well-established therapy for the secondary prevention of cardiovascular events. However, its role in the primary prevention of cardiovascular disease is unclear, especially in older persons, who have an increased risk. Methods: From 2010 through 2014, we enrolled community-dwelling men and women in Australia and the United States who were 70 years of age or older (or =65 years of age among blacks and Hispanics in the United States) and did not have cardiovascular disease, dementia, or disability. Participants were randomly assigned to receive 100 mg of enteric-coated aspirin or placebo. The primary end point was a composite of death, dementia, or persistent physical disability; results for this end point are reported in another article in the Journal. Secondary end points included major hemorrhage and cardiovascular disease (defined as fatal coronary heart disease, nonfatal myocardial infarction, fatal or nonfatal stroke, or hospitalization for heart failure). Results: Of the 19,114 persons who were enrolled in the trial, 9525 were assigned to receive aspirin and 9589 to receive placebo. After a median of 4.7 years of follow-up, the rate of cardiovascular disease was 10.7 events per 1000 person-years in the aspirin group and 11.3 events per 1000 person-years in the placebo group (hazard ratio, 0.95; 95% confidence interval [CI], 0.83 to 1.08). The rate of major hemorrhage was 8.6 events per 1000 person-years and 6.2 events per 1000 person-years, respectively (hazard ratio, 1.38; 95% CI, 1.18 to 1.62; P<0.001). Conclusions: The use of low-dose aspirin as a primary prevention strategy in older adults resulted in a significantly higher risk of major hemorrhage and did not result in a significantly lower risk of cardiovascular disease than placebo.